Pelindian Logam Tanah Jarang dari Terak Timah dengan Asam Klorida setelah Proses Fusi Alkali - Trinopiawan, Kurnia; Mubarok, Mohammad Zaki; Mellawati, June; Ani, Budi Yuli (BRIN Publishing, 2016)
Tin slag, a waste product from tin smelting process, has a potency to be utilized further by extracting the valuable metals inside, such as rare earth elements(REE). The objective of this study is to determine the optimum leaching condition of REE from tin slag after alkali fusion. Silica structure in slag is causing the direct leaching uneffective. Therefore, pre-treatment step using alkali fusion is required to break the structure of silica and to increase the porosity of slag. Fusion is conducted in 2 hours at 700 oC, with ratio of natrium hidroxide (NaOH) : slag = 2 : 1. Later, frit which is leached by water then leached by chloride acid to dissolve REE. As much as 87,5% of REE is dissolved at 2 M on chloride acid (HCl) concentration, in 40o C temperature, -325 mesh particle size, 15g/100ml of S/L, 150 rpm of agitation speed, and 5 minutes of leaching time.